PENGARUH TINGKAT PENGETAHUAN DAN PERSEPSI KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN OBAT GENERIK DI KOTA - Hendarwati, Atik; Marsila, Evi (PRIMA EKONOMIKA, 2022)
his study aims to determine the effect of Knowledge Level and Consumer Perception on the Decision to Purchase Generic Drugs in Yogyakarta City. This type of survey research with quantitative associative approach. The population is the people of Yogyakarta City who have ever consumed generic drugs, the research sample is 100 respondents, purposive sampling. Research data includes primary data and secondary data. The results of the t test show that there is a significant effect of Knowledge Level on Purchase Decisions (0.000 < 0.05); Consumer Perception has a significant effect on Purchase Decisions (0.000 < 0.05). The results of the F test show that there is a significant effect of the level of knowledge and consumer perceptions simultaneously on purchasing decisions (0.000 < 0.05). The regression equation shows that the coefficient of Knowledge Level and Consumer Perception are both positive, meaning that the increasing Knowledge Level and Consumer Perception will be followed by an increase in Purchase Decision. Adjusted R2 value that the Level of Knowledge and Consumer Perception is able to explain the Purchase Decision of 66.5%. The strong relationship between Knowledge Level and Consumer Perception of Purchase Decisions is 82% or very strong. Keywords: Purchase Decision, Knowledge Level, Consumer Perception, Generic Drugs